A Mother Who Experienced TRALI After a Caesarian Section on the Indication of Severe Pre-eclampsia with a Macrosomic Fetus - Lestari, Puti Fajri; Satria, Pom Harry (Fakultas Kedokteran Universitas Andalas, 2025)
Introduction: Transfusion-Related Acute Lung Injury (TRALI) is a severe, often fatal, complication of blood transfusion. Obstetric patients with severe pre-eclampsia are uniquely susceptible due to a